'Sustainability, in other Words Responsibility for the Future, is Fundamentally a Question of Values.' - Hornyik, Zsuzsanna (Public Finance Quarterly, 2023)
Interview with Dr. György Kocziszky, Member of the Monetary Council of the Central Bank of Hungary (Magyar Nemzeti Bank)